The Motivation of Independent Value Creation by Fans of ‘Fostered Idols’ in China - Zhang, Yue (2020)
Value creation is an important subject in marketing research and practices. Scholars have noticed the changes in the role that companies and consumers play in value creation process, and defined the value creation behaviour carried out by customers spontaneously without the participation of companies as ‘independent value creation’. In the studies of independent value creation, behaviour of fans of ‘fostered idols’ provided material for this topic. ‘Fostered idols’ are produced under a new mode influenced by Japanese and Korean culture with the marketing strategy of deep participation of fans, both online and offline, to develop loyalty to idols and actively create value. This dissertation takes independent value creation behaviour of fans of ‘fostered idols’ as the research object, exploring the motivation of fans to perform value creation behaviour in fan community. The methodology is grounded theory and the primary data is obtained from in-depth interviews with 10 fans of a teenage idol group R1SE. Through coding, the results show that the motivations of independent value creation by fans of ‘fostered idols’ can be divided into prepositive motivations and consequential motivations, in which fan culture also influences the process. Finally, according to the conclusion, the management implication is put forward from the perspective of brand establishment.